Biocomputational-mediated screening and molecular docking platforms for discovery of coumarin-derived antimelanogenesis agents - Lim, Jing Yu; Gew, Lai Ti *; Tang, Yin Quan * (Medknow Publications, 2023)
Background: Hyperpigmentation occurs when excess melanin accumulates in the skin and causes the skin to become darker in color. Pursuing attractive appearance and colorism have promoted the development of the skin whitening market globally. The proteins targeted in this research are tyrosinase-related protein 1, cyclic adenosine monophosphate response element-binding protein, receptor tyrosine kinase, and endothelin receptor type B.